REPRESENTASI PEREMPUAN MASKULIN DALAM FILM MENCURI RADEN SALEH KARYA ANGGA DWIMAS SASONGKO - Yolanda Christin, Urimiana; Nur Suryanto Gono, Joyo; Sunarto, Sunarto (Interaksi Online, 2024)
The construction of women in society with the existence of feminine and masculine characters in the midst of a patriarchal culture then seems to provide restrictions and place women in a subordinate position. Women are labeled with feminine traits as weak people under men who are considered superior with the label of masculine traits. This phenomenon then becomes the background of this research, based on the theoretical stand point in the critical paradigm by using the method of analyzing the five codes of Roland Barthes’ semiotic lexia reading. The results of this study indicate that the female characters in Stealing Raden Saleh are portrayed masculine by having dominant, confident, strong, and assertive traits. These traits are the traits of masculine characters. This depiction defies the myth that develops in society if women are figures who are required to have feminine traits and become weak people under the masculine domination of men. When women are constructed in a masculine way and have traits of masculine characters, they can be called masculine women and androgynous individuals. An androgynous individual is an individual who has both masculine and feminine traits at the same time.